2005
DOI: 10.1002/bit.20741
|View full text |Cite
|
Sign up to set email alerts
|

A new approach for modelling simultaneous storage and growth processes for activated sludge systems under aerobic conditions

Abstract: By critically evaluating previous models, a new mechanistic model is developed to describe simultaneous storage and growth processes occurring in activated sludge systems under aerobic conditions. Identifiability was considered an important criterion during the model development since it among others helps to increase the realiability and applicability of models to full-scale WWTPs. A second order model was proposed for description of the degradation of the storage products under famine conditions. The model i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
109
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(114 citation statements)
references
References 34 publications
4
109
0
1
Order By: Relevance
“…For microbial sludge treatment plant biomass growth rate is relatively low and-as confirmed experimentally-accumulation is the predominant reaction (Sin et al [5]). Numerous studies confirm that the observed changes in the transient behaviour of activated sludge are related to the changes in metabolic pathways corresponding to the primary and secondary growth phases.…”
Section: Primary and Secondary Growth Of Microorganismsmentioning
confidence: 95%
“…For microbial sludge treatment plant biomass growth rate is relatively low and-as confirmed experimentally-accumulation is the predominant reaction (Sin et al [5]). Numerous studies confirm that the observed changes in the transient behaviour of activated sludge are related to the changes in metabolic pathways corresponding to the primary and secondary growth phases.…”
Section: Primary and Secondary Growth Of Microorganismsmentioning
confidence: 95%
“…For the model calibration, the initial concentration of active biomass X Hð0Þ , was estimated using the initial OUR level (Eq. (7)) without any substrate addition [35].…”
Section: Parameter Calibration and Simulationmentioning
confidence: 99%
“…Parameters are assigned with initial values for calibration from literatures as shown in Table 6. 10,29 In this work, the most important model output variables of COD, NH 4 þ -N and MLVSS concentrations are analyzed as shown in Figures 2-4.…”
Section: Sensitivity Analysismentioning
confidence: 99%